Akuntabilitas Program Sekolah Berbasis Outcome-Based Education - zahwa, nadilatu; Zahra, Hesty; Ramadhaniati, Aulia; Rahayu, Annisa; Maulida, Najwa; ., Suhaimi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Ensuring that educational programs produce measurable learning outcomes requires a strong accountability system within schools. This study examines school program accountability through the perspective of Outcome-Based Education (OBE), an educational approach that emphasizes student competency achievement as the primary indicator of learning success. The research applies a qualitative approach using a literature review method by analyzing various academic journals, books, and scholarly publications related to school management and the implementation of OBE. Data were collected through documentation techniques and analyzed descriptively to identify major concepts of accountability in educational management. The findings indicate that accountability in the OBE framework highlights transparency in program implementation, effective educational management, and the achievement of student learning outcomes. In addition, active involvement of stakeholders such as teachers, parents, and the community becomes an essential component in maintaining accountability. Continuous evaluation and systematic reporting also play an important role in ensuring that educational programs are implemented effectively and improved over time. Therefore, implementing school accountability based on OBE can contribute to improving educational quality and supporting sustainable development of student competencies.